2015
DOI: 10.1007/s10897-015-9826-8
|View full text |Cite|
|
Sign up to set email alerts
|

Using ApoE Genotyping to Promote Healthy Lifestyles in Finland – Psychological Impacts: Randomized Controlled Trial

Abstract: Common health recommendations often incite very little public response, as people instead require individualized information. The purpose of this study was to assess the psychological effects of personal genetic information, provided by different apoE genotypes, as a tool to promote lifestyle changes. This study was a one-year intervention study using healthy adults, aged 20-67 years (n = 107). Their experiences of state anxiety, threat and stage of change were measured three times over a 12 months period. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 56 publications
1
33
0
Order By: Relevance
“…group sizes, only one biomarker, randomization and lack of background variables) have been reported in our previous studies [26] [27].…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…group sizes, only one biomarker, randomization and lack of background variables) have been reported in our previous studies [26] [27].…”
Section: Discussionmentioning
confidence: 85%
“…The baseline and follow-up assessments included detailed measurements of psychological (threat and anxiety experience, stage of change), [26] and behavioral (dietary fat quality, consumption of vegetables-high fat/sugar foods and-alcohol, physical activity and health and taste attitudes) [27] and clinical factors ( Table 1). During the intervention six different communication sessions (lectures on healthy lifestyle and nutrigenomics, health messages by mail, and personal discussion with the doctor) were arranged.…”
Section: Study Design and Participantsmentioning
confidence: 99%
See 2 more Smart Citations
“…296 An intervention to improve diet quality based on personalized advice for genotype at APOE found that high-risk individuals who received personalized dietary advice were more likely to make short-term dietary improvements compared with low-risk or control subjects. 297 Although consumers are more engaged when receiving personalized dietary advice, the higher initial motivation may not lead to sustained long-term implementation of dietary changes. However, even if the hurdles of implementation and longterm patient motivation are overcome, the main obstacle to personalized nutrition lies in establishing sufficient scientific evidence to make informed and efficacious recommendations.…”
Section: Personalized Nutritionmentioning
confidence: 99%